Product Quality and Brand Image towards Customers' Satisfaction through Purchase Decision of Wardah Cosmetic Products in Surabaya - Ernesto Jose Tjahjono; Lena Ellitan; Yuliasti Ika Handayani (Program MM Universitas Surabaya, 2021)
This study aims to determine and examine the effect of product quality on purchasingdecisions, the influence of brand image on purchasing decisions, the influence ofpurchasing decisions on customer satisfaction, the effect of product quality oncustomer satisfaction through purchasing decisions, and the influence of brand imageon customer satisfaction through purchasing decisions. This research is in the form ofquantitative research, where the data obtained is primary data obtained throughdistributing questionnaires to 120 respondents who have made purchases of Wardahcosmetic products. The data obtained were then processed using the Smart PLSsoftware. The results showed that there was a positive and significant relationshipbetween product quality and brand image variables on purchasing decisions, whichmeans that good product quality and good brand image will create purchasingdecisions for consumers. Purchase decisions have a positive influence on customersatisfaction. Product quality has a positive and significant effect on customersatisfaction. Brand Image does not significantly influence customer satisfaction.Product quality and brand image have a positive and significant effect on customersatisfaction through purchasing decisions. This shows that consumers will be satisfiedwith a product when consumers are satisfied with the purchasing decisions made onthe product.